Does initial vocational training foster innovativeness at the company level? Evidence from German establishment data - Eike Matthies; Katarzyna Haverkamp; Jörg Thomä; Kilian Bizer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
While an increasing number of conceptual studies postulate that vocational education and training (VET) activities have a positive impact on firm-level innovation, empirical evidence on the subject remains scarce. This study exploits establishment data from a representative survey of German companies to estimate the association between firms' participation in initial VET and their innovation outcomes. The results based on linear probability models and entropy balancing show that the relationship between VET activity and innovation are more ambiguous than often postulated. Overall, the participation in initial VET has virtually no effect on radical product innovation. However, a positive association between VET activities and incremental product innovation or process innovation is found in the case of microenterprises with fewer than 10 employees. From this, we conclude that participation in the VET system primarily promotes the innovation and learning conditions of very small training enterprises. The paper concludes with implications for policy and research.
Keywords: I20; J24; O31; 330; Vocational education; apprenticeship training; modes of innovation; innovation without R&D; SMEs